Subtle Discrimination at Work: British Ethnic Minority Graduate Perspectives - Bell, Ashley (2016)
This Qualitative research hopes to understand the underlying processes of subtle discrimination in the graduate workplace. This is done with the use of diary data and 17 interviews of second-generation minorities from a range of ethnic backgrounds. We argue that subtle discrimination within a graduate workplace manifests itself through 4 key processes of power. These processes include; Installation, the process of introducing racial difference into the office setting and commencing the judging of minorities. Normalisation, the process of setting this difference as the status quo, usually through introducing racial discussion into group contexts. Thirdly acceptance, a process novel to graduate workplaces, in which minorities rationalise their prospects to accept discrimination and finally the process of correction which as well as acceptance works to solidify the status quo but instead, correction works through shunning and complimenting ethnic minorities.